Sensor technology implementation for research, treatment, and assessment of eating disorders. Issue 10 (13th June 2019) - Levinson, Cheri A.; Christian, Caroline; Shankar‐Ram, Shruti; Brosof, Leigh C.; Williams, Brenna
Abstract: Sensor technology has made huge technological advances in the past decade. Many sensor technologies (e.g., wearable wristbands) have been integrated into health research with the ability to substantially improve health outcomes and reduce health care costs. Despite the rapid technological developments in sensor technology, little research has examined sensor technology in eating disorders (EDs). The overarching aim of the current article is to briefly review the literature on sensor technology and health outcomes, including EDs, and discuss several potential ideas for the application of sensor technology in the treatment, assessment, and diagnosis of EDs. We will also present data from a feasibility case study with an ED participant and healthy control providing a brief example of how wearable sensor technology might be implemented in ED research. Overall, we will discuss how sensor technology could be used to improve treatment and assessment of EDs and represents an idea in need of more research in the ED field.